Deferred versus conventional stent implantation in patients with ST-segment elevation myocardial infarction (DANAMI 3-DEFER): an open-label, randomised controlled trial. Issue 10034 (28th May 2016) - Kelbæk, Henning; Høfsten, Dan Eik; Køber, Lars; Helqvist, Steffen; Kløvgaard, Lene; Holmvang, Lene; Jørgensen, Erik; Pedersen, Frants; Saunamäki, Kari; De Backer, Ole; Bang, Lia E; Kofoed, Klaus F; et al.
Summary: Background: Despite successful treatment of the culprit artery lesion by primary percutaneous coronary intervention (PCI) with stent implantation, thrombotic embolisation occurs in some cases, which impairs the prognosis of patients with ST-segment elevation myocardial infarction (STEMI). We aimed to assess the clinical outcomes of deferred stent implantation versus standard PCI in patients with STEMI. Methods: We did this open-label, randomised controlled trial at four primary PCI centres in Denmark. Eligible patients (aged >18 years) had acute onset symptoms lasting 12 h or less, and ST-segment elevation of 0·1 mV or more in at least two or more contiguous electrocardiographic leads or newly developed left bundle branch block. Patients were randomly assigned (1:1), via an electronic web-based system with permuted block sizes of two to six, to receive either standard primary PCI with immediate stent implantation or deferred stent implantation 48 h after the index procedure if a stabilised flow could be obtained in the infarct-related artery. The primary endpoint was a composite of all-cause mortality, hospital admission for heart failure, recurrent infarction, and any unplanned revascularisation of the target vessel within 2 years' follow-up. Patients, investigators, and treating clinicians were not masked to treatment allocation. We did analysis by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01435408 . Findings: Between March 1, 2011, and Feb 28, 2014, we randomly assigned 1215 patients to receive either standard PCI (n=612) or deferred stent implantation (n=603). Median follow-up time was 42 months (IQR 33–49). Events comprising the primary endpoint occurred in 109 (18%) patients who had standard PCI and in 105 (17%) patients who had deferred stent implantation (hazard ratio 0·99, 95% CI 0·76–1·29; p=0·92). Procedure-related myocardial infarction, bleeding requiring transfusion or surgery, contrast-induced nephopathy, or stroke occurred in 28 (5%) patients in the conventional PCI group versus 27 (4%) patients in the deferred stent implantation group, with no significant differences between groups. Interpretation: In patients with STEMI, routine deferred stent implantation did not reduce the occurrence of death, heart failure, myocardial infarction, or repeat revascularisation compared with conventional PCI. Results from ongoing randomised trials might shed further light on the concept of deferred stenting in this patient population. Funding: Danish Agency for Science, Technology and Innovation, and Danish Council for Strategic Research.